2020
DOI: 10.1186/s12872-020-01370-y
|View full text |Cite
|
Sign up to set email alerts
|

Patient-level factors influencing hypertension control in adults in Accra, Ghana

Abstract: Background: Effective control of blood pressure is necessary to avert the risk of cardiovascular diseases from uncontrolled hypertension. Despite evidence on the benefits of hypertension control, rates of control in Ghana remain low. This study assessed the patient-level factors that influence hypertension control among adults in Accra, Ghana. Methods: A total of 360 hypertensive patients from two hospitals in Accra, Ghana were enrolled in the study. Patient socio-demographic characteristics were tabulated and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 36 publications
(48 reference statements)
0
28
0
1
Order By: Relevance
“… 13 Silent clinical picture and higher prevalence of hypertension, low people awareness (43%), poor adherence to antihypertensive medication, bad dietary habits, and high costs of drugs contribute to poor BP control. 5 , 14 16 Moreover, in developing countries, government priority is given to acute disorders, child and maternal health care, and control of communicable diseases, giving very little emphasis on chronic non-communicable diseases. 4 …”
Section: Introductionmentioning
confidence: 99%
“… 13 Silent clinical picture and higher prevalence of hypertension, low people awareness (43%), poor adherence to antihypertensive medication, bad dietary habits, and high costs of drugs contribute to poor BP control. 5 , 14 16 Moreover, in developing countries, government priority is given to acute disorders, child and maternal health care, and control of communicable diseases, giving very little emphasis on chronic non-communicable diseases. 4 …”
Section: Introductionmentioning
confidence: 99%
“…Stopping medication when symptoms disappear, fear of addiction and side effects have been reported in other studies [ 11 , 43 ]. Our study also showed that physicians felt that fear of side effects from long term medication use contributed to patient non-adherence to antihypertensive medications.…”
Section: Discussionmentioning
confidence: 67%
“…Counseling alone or counseling combined with patient training improved BP control in another study [ 42 ]. A systematic review of qualitative studies from 16 countries, including Tanzania [ 11 , 43 ], showed that many patients intentionally reduced or stopped treatment without consulting their physicians. Patient-centric care and engaging patients in shared decision making have both been identified as important facilitators in addressing barriers to medication adherence [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some essential parameters which are used for the evaluation of patient's knowledge, which includes the name, the dose, the dosing frequency, the duration of therapy and one common side effect of the medicine (Saqib et al, 2019) . In Ghana, though there have been studies on patients knowledge on NCDs (Agyei-Baffour et al, 2018;Boima et al, 2015;Marfo and Owusu-Daaku, 2017;Okai et al, 2020) there appears to be paucity of data on co-morbid hypertension and diabetes patients regarding their knowledge about medication and therapy in hospital settings. This study therefore seeks to assess the knowledge of patients with hypertension and type-2diabetes mellitus at a municipal hospital in Ghana about their medications and therapy.…”
Section: Introductionmentioning
confidence: 99%